Armenia : Implications of the Global Economic Crisis for Poverty - World Bank (World Bank, 2012)
The global economic crisis seriously threatens the economic growth and poverty reduction that Armenia achieved in recent years. The most recent data indicate that the economy is now shrinking, with prospects worsening in 2009 and 2010 when the full impact of the crisis is expected to unfold. These developments are a setback for Armenia after a decade of nearly double-digit growth and substantial poverty reduction. Depending on the depth of the crisis in Armenia, in its main trading partners, and in its migrant workers' host countries, and depending on the effectiveness of policy responses, the crisis could have a protracted negative effect on Armenians' living standards. The economic downturn, coming on the heels of the food and fuel price increases last year, will have particularly difficult consequences for the poor and vulnerable who have limited coping means to deal with these successive shocks. The note identifies the main channels of transmission to households of the current global economic crisis and estimates its potential impact on poverty in Armenia. Given uncertainties regarding the scale of the crisis and how households are likely to cope, the note is intended to provide indicative estimates of the poverty impact of the crisis, rather than precise estimates. These estimates are made by simulating the effects of the anticipated slowdown on household consumption using data from the 2007 Integrated Living Conditions Survey (ILCS). The key messages that come out of the analysis are that the crisis will have potentially serious implications for poverty and that this calls for significant responses by the Government of Armenia and its development partners. The government is taking a number of steps to provide protection to the poor, including the protection of public spending on social protection and other pro-poor programs and to improve the targeting efficiency of the programs. These measures should help lessen the impact of the crisis on the poor and the vulnerable.